2008
DOI: 10.1007/s00264-007-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Does bone impaction technique reduce tunnel enlargement in ACL reconstruction?

Abstract: The aim of this study was to investigate effects of bone impaction technique on tunnel enlargement after ACL reconstruction at a minimum 2 years follow-up. Two groups of patients who had been operated upon with the same arthroscopic technique with the exception of tibial tunnel constitution were compared. Twenty-one patients of group A (drilling to 6 mm followed enlargement to 8-9 mm by using dilators) and 23 patients of group B (directly drilling to the size of the graft) were evaluated clinically and radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…Such injuries can loosen the tunnel wall and cause TW or fixation failure. A previous study used a dilator to create more compact bone on the tunnel wall and reported less TW than with reaming alone 19. We also used a bone dilator on the tibial tunnel to prevent TW, and our results also showed a successful reduction in TW.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Such injuries can loosen the tunnel wall and cause TW or fixation failure. A previous study used a dilator to create more compact bone on the tunnel wall and reported less TW than with reaming alone 19. We also used a bone dilator on the tibial tunnel to prevent TW, and our results also showed a successful reduction in TW.…”
Section: Discussionsupporting
confidence: 51%
“…These are known to cause TW. To prevent TW and to increase the compactness of the bone around the tunnel, a previous researcher had used a dilator with bone impaction 19. However, bone impaction using a dilator could result in a cortical bone fracture on the articular side.…”
Section: Methodsmentioning
confidence: 99%
“…We have observed tunnel enlargement in the early postoperative period (2 weeks) probably because we have used extraction drilling. 29,30 A possible solution to this problem may be to drill 1 mm smaller than measured graft diameter and then enlarge to appropriate diameter with a tunnel dilator. 29 Another possible cause for early tunnel enlargement may be the early aggressive, braceless rehabilitation protocol that we have followed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be possible to overcome the size constraints of anatomical single bundle ACL reconstruction if we use rounded rectangle ACL reconstruction. In addition, a drill heats the bone [21] , while a dilator does not heat the bone and may prevent tunnel widening by compressing the cancellous bone [22] . However, further investigation is needed to address these issues.…”
Section: Discussionmentioning
confidence: 99%